L. Currie and A. O. Hirschman on development as a problem of decision making (2018)
This work analyzes the contributions of L. Currie and A. O. Hirschman to development theories. We show that traditional approaches to the divergence between these authors have overlooked some common views in their development strategies. For both, the catalyst role played by the experts -being facilitators of decision-making processes- is crucial for triggering economic transformation. Using evidence from both their published works and archival documents little exploited in the literature, we show that their experiences as experts in Colombia led them to refine their ideas on development and to appraise the importance of the political economy of expertise.